PERAN GERAKAN LITERASI DAN MINAT BACA DALAM MEMBENTUK KARAKTER RELIGIUS SISWA - ANIK ZUROIDAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Literacy culture is no longer foreign. Especially in the world of education. But not many know what activities are included in it. An online information states that literacy culture is intended to carry out habits of mind which are followed by reading and writing processes, which in the end can create a work. In Islam, the foundation for literacy activities is very strong. This can be seen in the Al-Alaq verse 1 of the Qur'an, which means: